PENGARUH PENERAPAN MEDIA PEMBELAJARAN KAHOOT UNTUK MENINGKATKAN MINAT BELAJAR IPAS KELAS V SDN 15 PEMULUTAN - Revita Dwi Cahyani; Middya Boty; Ines Tasya Jadidah (STKIP Subang, 2026)
This study aims to determine the effect of implementing Kahoot learning media on students' interest in learning Science (IPAS) in 5th grade at SDN 15 Pemulutan. This research is motivated by the low interest of students in learning, characterized by a lack of attention and participation during the teaching and learning process. The research method used is a quantitative method with a Pre-Experimental design (One-Group Pretest-Posttest). The research instrument used was a questionnaire on interest in learning. Data analysis techniques included validity tests, reliability tests, normality tests, and hypothesis testing using the Paired Sample t-test. The results showed that the average pretest score was 33.10 and the average posttest score was 48.87. Hypothesis testing results obtained a significance value of 0.000 < 0.05, meaning that H₀ is rejected and H₁ is accepted. Thus, it can be concluded that there is a significant influence of the application of Kahoot learning media on the interest in learning IPAS of 5th grade students at SDN 15 Pemulutan.